Potency of Cocoa Honey, Byproduct of Cocoa Bean Processing as Probiotic Media: Optimization of Saccharomyces boulardii Growth and Its Antimicrobial Activity - Neti Yuliana; Fibra Nurainy; Sumardi Sumardi; Zikrina Marentina; Nabila Rizka Putri (Journal of Multidisciplinary Applied Natural Science, 2025)
Cocoa honey, a byproduct of cocoa bean processing, contains high sugars and minerals; thus, it has potential as a fermentation medium. This research investigated the potency of cocoa honey as probiotic media for promising yeast probiotic Saccharomyces boulardii. The growth of S. boulardii in the cocoa honey medium was optimized through response surface methodology employing a central composite rotatable design to obtain maximum cell production and antimicrobial activity. The effects of inoculum size (2–5%), sucrose addition (2.0–3.0%), and fermentation time (5–20 h) were evaluated. The agar diffusion technique assessed the cocoa honey medium's antibacterial activity. Results showed that these independent variables significantly affected the production of S. boulardii cells and their microbial activity against Escherichia coli. The optimal values generated by the model with a desirability value of 0.908 were 20 h of fermentation time, 2% of sucrose addition, and 2% of inoculum size. The maximum yeast count (log10 8.07 cells/mL) and antibacterial activity (4.88 mm) were reached under these optimized conditions, which agreed with the predicted value of the RSM model. This study provided valuable information on the potency of cocoa honey as a fermentative medium for applying S boulardii to develop a probiotic drink.